Efficacy of ultrasound guided venous cannulation positioning during venous-arterial extracorporeal membrane oxygenation - Sun, Yuanyuan; Huang, Chengmin; Ou, Weimei; Liu, Zhixian; Sun, Guangfeng; Zhang, Xinchen; Chen, Xu; Wang, Bin; Zhang, Guoming (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the clinical impact of ultrasound-guided venous cannulation positioning during the initiation of venous-arterial extracorporeal membrane oxygenation (VA-ECMO).MethodsThis retrospective study included 48 patients who received bedside VA-ECMO support between June 2019 and August 2024. Patients were divided into an ultrasound-guided group (UG, n = 23) and conventional body surface landmark group (BSL, n = 25). Clinical outcomes, cannula positioning accuracy, complications, infection markers, and prognosis were compared. A subgroup analysis was performed in patients who did not undergo cardiopulmonary resuscitation (non-CPR).ResultsCompared to BSL group, patients in the UG group had significantly higher rates of optimal venous cannula positioning (p < 0.01), lower incidence of unstable flow and pulmonary edema, and shorter aortic valve closure time, infection markers (WBC, PCT) were also significantly lower in the UG group (p < 0.05). In the non-CPR subgroup, the UG group had shorter ECMO duration, hospital stay, and dual antibiotic therapy duration (all p < 0.05), with non-significant trends toward better survival.ConclusionUltrasound-guided venous cannulation improves cannula positioning accuracy, reduces early complications, and may enhance clinical outcomes, particularly in non-CPR patients. Routine use of ultrasound guidance is thus recommended in bedside VA-ECMO procedures.